The vertical disintegration of ship management: choice criteria for third party selection and evaluation - Cullinane, Kevin P B; Panayides, Photis (My University, 2002)
An assessment of the rationale for the vertical disintegration of ship management suggests that there might be compelling economic benefits for the separation of ownership from management. In this context, as a means for developing effective marketing strategies, it is important for ship managers to know the criteria used by current and prospective clients for ship manager selection and evaluation. The aim of this paper is to empirically identify the dimensions for ship manager selection and performance evaluation and their relative importance and to discuss the implications for marketing emanating from such an assessment. The methodology adopted includes the collection of secondary and primary data, both from ship managers and their clients, using interviews and a mail survey. The results indicate the prevailing importance of certain dimensions in selection (e.g. technical ability, reputation, competency) and evaluation (responsiveness, trustworthiness, technical ability), whereas it also found that price alone is not perceived to be as important in ship manager selection. It is concluded that placing emphasis on such dimensions in the formulation of a marketing strategy will contribute towards the attraction and retention of clients, whereas cost-cutting measures to allow price reduction, as well as advertising, will be ineffective over the long term
Keywords: Shipping--Management; Shipping; Transportation; Maritime economics